Teachers’ perceptions of principals best practices to conflict management at the Islamic Private Secondary Schools, Yala Province, Thailand - Salleh, Mohamad Johdi; Adulpakdee, Apitree (2011)
This study presents the perceptions of teachers toward the best practices of principals’ conflict management at the selected Islamic Private Secondary Schools in Yala Province Thailand. The sample of the study was 302 teachers. The instruments used were survey questionnaire of fifteen items and followed by interview with the conveniently selected ten respondents. The data was processed using the Statistical Package for Social Science (SPSS) version 17.0 for Windows. The findings of the study show that the highest three best practices of conflict management among principals as perceived by the teachers were item 4 ‘Compromise is the best strategy for managing conflict’ with 91.4 or 276 respondents agreed, item 3 ‘Conflict management needs an involved process of joint exploration for solution’ with 91.1% agreed, and, item 7 ‘Conflicts can be solved if the parties understand each other, and jointly search for alternative solutions’ with 90% or 262 agreed. On the other hand, the least response was item8 ‘The more powerful you are, the more effectively you can resolve the conflicts’ with only 30.4% respondents agreed. As an addition, this study also discusses the principal best practice towards conflict management as perceived by teachers in the interviews especially from the Islamic perspectives. It is hope that the findings of this study may guide the principals, teachers and all group or individual in educational organization to manage conflicts wisely and successfully.